GUIDANCE AND COUNSELING PROGRAM (FOCUSING ON PERSONAL-SOCIAL) TO IMPROVE STUDENT RESILIENCE - Fahriza, Irfan; Karima, Yuniar; Rayaginansih, Syari Fitrah; Julius, Andre (IKIP Siliwangi, 2021)
This research is motivated by the phenomenon of adolescent maladjustment behavior. In this study, adolescents' wrong behavior is considered the impact of adolescents' failure in facing adversity conditions in their lives. The individual's ability to deal with adversity conditions is known as resilience. This research's product is the design of a personal social counseling and guidance program that is hypothetically effective in increasing students' resilience. The research method uses a quantitative approach, with descriptive methods. This study population was 414 students of class X SMK Profita Bandung and 157 students as a sample. The research sample was taken using a simple random sampling technique; that is, the research sample was obtained randomly. This study resulted in (1) an overview of the resilience of class X students of Profita Vocational School, Bandung City, most of whom are in the medium category; (2) there is no significant difference between the level of resilience of students from intact families with students from not intact; and (3) the design of a hypothetical social, personal counseling and guidance program to increase the resilience of students. The results of this study are recommendations for (1) guidance and counseling teachers, as a follow-up effort in implementing social, personal guidance and counseling programs in increasing the resilience of students that have been designed; (2) The next researcher can continue the research conducted by the researcher and look for methods or techniques that are more effective in increasing student.